IDEAS OF CENTRAL ASIAN AND EUROPEAN SCHOLARS ON CREATIVE AND LOGICAL THINKING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents a comparative analysis of the ideas of Central Asian and European scholars on thinking. The study identifies common and distinct aspects of developing creative and logical thinking, and explores the application of historical-philosophical sources in pedagogical practice. The results contribute to optimizing the development of creative and analytical thinking in modern education.